Engagement in social activism and its implications on social responsibility - Abeysinghet, Shantha; Nor, Sharifah; Hamzah, Azimi; Tamam, Ezhar (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
The shape of the future social world is related directly to the socialization process of young people. Incidentally, many social institutions play a significant role to empower young people to meet both local and global challenges. Though, the technological and scientific development boost has to a great extent destabilized civic and social protection of the global. In this context, social activism can emerge as a means for civic engagement and citizenship building among young people. This study involved, campus youths in Sri Lanka and was conducted using the adopted Instrument of Corning’s measures of social activism orientation. Four hundred and forty nine subjects were randomly selected from the six campuses representing, three faculties (Science, Arts & commerce/Management): Profile of respondents indicated wider access to higher education in Sri, Lanka since universal free education exit from primary level to university level. There were significant relationship between social activism and contextual factors and demographic factor. Policy recommendation for successful civic and democratic participation and positive youth development IS discussed with special attention to the development of social responsibility and pluralist culture at higher educational institutions.